A Case of Malignant Course of Right Coronary Artery: Frequent Angina in Young Person - Sidhi Laksono Purwowiyoto; Steven Philip Surya (Cardiovascular and Cardiometabolic Journal, 2021)
Congenital anomalous coronary artery is a rare condition, but it might be the biggest pitfall for cardiologist. It might be silent until the patient reach young adult and has high intensity activity. Symptomatic anomalous course of coronary artery has wide spectrum from asymptomatic until the lethal one. We present a case of young adult with activity-triggered atypical chest pain and diagnose with anomalous origin of right coronary artery (RCA) from the left coronary sinus with inter-arterial course between the aorta and the main pulmonary artery that was detected by CT coronary angiography. This anomaly has been called malignant course RCA. Coronary artery anomaly is a congenital condition. Most of the cases are remain asymptomatic. This condition also one of the most cause for sudden cardiac death because the coronary artery examination is not regularly done. Nevertheless, during high intense activity, it will be symptomatic and might be lethal. Diagnose coronary artery anomalies might be tricky and cardiologist must be aware with this. More devastating, no firm guideline in treatment of right anomalous coronary artery from opposite sinus. Keywords: Chest Pain, CT Coronary Angiography, Malignant RCA